The Human Measurements of the Modern Educational Process - Fedir Vlasenko; Yevheniia Levcheniuk (International Society of Philosophy and Cosmology, 2024)
The human-centric approach to the modern educational process emphasizes individuality, personal development, and the consideration of each pupil's or student's needs. The educational process extends beyond the mere transmission of knowledge, aiming instead for a profound understanding of each student's needs, interests, abilities, and unique characteristics. This organization of the education system necessitates individualization and differentiation. Curricula and teaching methods are tailored to the specific needs and capabilities of each student. This approach involves employing varied strategies, methods, and learning paces depending on individual characteristics. Modern education fosters the development of critical thinking and creativity, as well as analysis and problem-solving skills, thereby stimulating students' creativity and innovative approaches. It also promotes social and emotional development by supporting the growth of students' social and emotional skills, responsibility, cooperation, and interaction with others. To encourage active student participation in the learning process, a variety of interactive methods, project work, and group assignments are utilized. The human dimension of the educational process is defined not only by its content but also by the methods and forms of organizing learning. These contribute to the comprehensive development of each student's personality, taking into account contemporary socio-cultural and technological realities.